Modelagem e simulação de aspectos hidrodinâmicos e cinéticos do processo de gaseificação de biomassa utilizando CFD - Braga, Marina Garcia Resende (Universidade Federal de São Carlos, 2017)
One of the major problems faced by humanity nowadays is the issue of preserving the environment. In recent years, progress has been accelerated, having a direct influence on the environmental impacts caused by several kinds of activities. In order to settle the situation, considering an industrial context, one of the alternatives is the use and generation of biofuels. One of the most ancient ways of energy generation is gasification, regarding biofuels, this process is a good alternative to contribute to environmental preservation. This work presents important points on the studying of biomass gasification process, evaluating hydrodynamic and kinetic aspects of the process through the use of numerical CFD (Computational Fluid Dynamics) simulation along with experimental data from literature. Firstly, the fluid dynamics was analyzed, not considering the occurrence of reactions. In this step of the project, the influence of high and low mass solid influxes in variables such as solid volumetric fractions (radial and axial) and particle velocities were verified. In addition, a study on how the restitution coefficient can have an effect on those variables were carried out. It was verified and influence of the coefficient on the solids volume fraction profiles in regions near to the risers walls. Moreover, a study of different drag models was also carried out, in order to obtain the best possible solids volume fraction profile. It was concluded that conventional drag models, such as Gidaspow et al. (1992), for example, are better in predicting the behavior of this variable in more dilute regions, while most models that consider a more heterogeneity in flows, such as those which use the Energy Minimization Multi-Scale (EMMS) approach, are better at predicting the same behavior in dense regions. Regarding the process kinetics, the influence of Gidaspow and EMMS models on the final process products conversion was also analyzed, as well as the solids volume fraction along riser height. The results showed that different drag models do not alter significantly this variable profile in this case.
Modeling and simulation of hydrodynamic and kinetic aspects of the biomass gasification process using CFD
Keywords: Gaseificação de biomassa; Fluidodinâmica; Cinética; Arraste; Fração volumétrica de sólidos; Biomass gasification; Fluid dynamics; Kinetics; Drag; Solids volume fraction; ENGENHARIAS::ENGENHARIA QUIMICA